FACTORS AFFECTING SUPPLY CHAIN PERFORMANCE: A QUANTITATIVE STUDY AMONG SMES IN THE FASHION INDUSTRY IN BANDUNG, INDONESIA - Ekoputri, Anissa Dyah; Apparavu, Kantharow; Singh , Jugindar Singh Katar (Electronic Journal of Business and Management, 2021)
Due to globalisation and technological changes, supply chain performance factors have become critical. This study addresses the lack of research on the combined effect of technology adoption, information dissemination, and human resources on supply chain performance in Bandung, Indonesia. Focusing on SMEs in the fashion industry, a quantitative survey was conducted with 82 SME owners. The results revealed that technology adoption has a significant relationship with supply chain performance. Surprisingly, information dissemination and human resources did not show a significant effect in this specific context. This study contributes to a better understanding of how Indonesian fashion SMEs can optimize their supply chains through technology.